Awareness and Perceptions of HPV and Cervical Cancer Prevention among School Adolescents: A Cross-Sectional Survey - Divakar, Hema (British Journal of Healthcare and Medical Research, 2025)
Background: Cervical cancer remains a leading cause of cancer-related mortality among women in India. Despite the availability of effective vaccines against Human Papillomavirus (HPV), the uptake remains low due to a lack of awareness and misinformation. Objectives: To assess the level of awareness, knowledge, and perceptions regarding cervical cancer and the HPV vaccine among school-going adolescents. Methods: A cross-sectional survey was conducted among students during a school health sensitization program. Structured questionnaires assessed knowledge of cervical cancer, awareness of HPV and its vaccine, vaccination status, and perceived barriers. Data were analyzed descriptively. Sample size 554 girls aged between 11 to 14 years as a part of awareness programme prior to school based HPV vaccination. Results: All participants (100%) were aware of the cervix and 95% had heard of cervical cancer. However, only 5% correctly identified HPV infection as the most common cause, with 42 respondents stating "don’t know." Only 13% had heard of the HPV vaccine, and just 20% had been vaccinated. All respondents agreed girls need HPV vaccination, and 50% correctly identified sexual contact as the mode of HPV transmission. Importantly, 100% expressed willingness to learn more. Notably, 75% were unsure of the recommended vaccination age. Lack of awareness (90%) and concerns about pain and side effects (55%) were the most cited barriers. Preferred channels for receiving information included school awareness programs and social media (80%). Conclusions: Despite high awareness of cervical cancer, there are significant gaps in knowledge about HPV and its vaccine. School-based awareness campaigns and adolescent-friendly communication strategies are urgently needed to improve vaccine literacy and uptake.